2018
DOI: 10.1016/j.jor.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of transforaminal lumbar interbody fusion in spondylolisthesis—A clinico-radiological correlation

Abstract: TLIF produces spinal fusion in most individuals. Strong spinal fusion is essential for good clinical outcome in spondylolisthesis patients who undergo TLIF. Reduction in slip is not necessary for all patients with listhesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…[ 36 ] Furthermore, a recent study by Balasubramanian et al also did not observe a positive effect of reduction grade on the outcome in patients undergoing TLIF. [ 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] Furthermore, a recent study by Balasubramanian et al also did not observe a positive effect of reduction grade on the outcome in patients undergoing TLIF. [ 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the long-term outcome, radiographic outcome parameters are not clearly connected with clinical outcome parameters yet. [15][16][17][18][19][20] Recently published results of 3-year follow-up outcome data of patients suffering from degenerative spondylolisthesis who underwent lumbar spinal fusion surgery showed that reduction of the sagittal rotation and the sacral inclination correlates with an improvement of clinical outcome scores collected by the Core Outcome Measure Index (COMI) and the Oswestry Disability Index (ODI). 21 This study sought to identify and define radiological parameters that are associated with a beneficial long-term clinical outcome 6 years after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…7 In a study by Balasubramanian et al, clinical and radiological correlations were performed and the study showed that 85% of the participants showed good clinical outcome at the end of 1 year. 8 Previously available literature has shown that symptomatic lumbar spondylolisthesis and spondylolysis can be efficiently managed by TLIF. 5 7 9 10 There is a gap in the available literature regarding the functional outcome of the patient in the postoperative period.…”
Section: Introductionmentioning
confidence: 99%